Safety, Efficacy and Acceptability of Early First Trimester Abortion using Oral Mifepristone and Sublingual Misoprostol - Shrestha, Deepak; Aryal, Shreyashi; Sharma, Binita (Journal of Nepal Health Research Council, 2018)
Background: With the legalization of medical abortion in Nepal, mifepristone-misoprostol combination via different routes has been widely used for early abortion. This study aims to evaluate the efficacy and acceptability of 200 milligrams mifepristone orally followed by 800 micrograms sublingual misoprostol in outpatient setting. Methods: It was an open-label prospective study conducted in outpatient department of a tertiary hospital over a period of 13 months. Clients upto nine weeks of pregnancy were enrolled. 200 milligrams of mifepristone orally followed by 800 micrograms of misoprostol sublingually 36 to 48 hours later were prescribed. They were followed up in 14 days sonologically or verbally through telephone. Side effects and satisfaction to the regimen were assessed through acceptability questionnaire. Mann-Whitney U test was used for analyzing categorical data. Results: A total of 47 clients were enrolled. The mean age and gestational age were 29.38 years (SD+5.914) and 6.2 weeks (SD+1.28) respectively. The commonest indications for termination were completed family and unwanted pregnancy (40.4% each). The average duration of bleeding was 5.76 days (SD +3.61). Abdominal cramping was the most common side effect (95.7%). The least acceptable parameter was the bleeding time (80.9%). For 97.9% clients, the adverse effects were acceptable. The overall success rate of the regimen was 87.2%. Conclusions: With a comparable success rate to vaginal use, home based sublingual use of misoprostol in low resource settings offers an acceptable and cost effective alternative for medical abortion upto nine weeks of pregnancy. Lesser gestational age is a useful predictor for successful abortion.